Informed trading, information asymmetry and pricing of information risk: Empirical evidence from the NYSE - Pradeep K. Yadav; Florian Bardong; Söhnke M. Bartram (University of Cologne, Centre for Financial Research (CFR), 2009)
We investigate and test hypotheses on how informed trading varies with market-wide factors and the structural and trading characteristics of a firm. We find strong evidence of commonality in informed trading, and a systematic dependence of informed trading on firm characteristics that is largely consistent with intuition and earlier theory and empirical evidence, wherever available. We accordingly decompose informed trading into two components: one that reflects information asymmetry with respect to skilled information processors with potentially private information on systematic factors or who generate a private informational advantage using public data; and another unpredictable component that reflects truly private information, potentially of traditional insiders. We test the pricing relevance of both these components and find that it is only the unpredictable component reflecting truly private information that is priced, and is priced more strongly and in a manner more robust than total informed trading. Our pricing-relevance results strongly support Easley and O'Hara (2004) and do not support Hughes, et al. (2007).
Keywords: G10; G12; G14; 330; Market microstructure; Common factors; Risk factors; Asymmetric information; Kapitalmarkttheorie; Wertpapierhandel; Asymmetrische Information; Informationseffizienz; Wertpapierbörse; USA